KPT6566 induces apoptotic cell death and suppresses the tumorigenicity of testicular germ cell tumors - Sun, Ruijing; Lee, Eun Joo; Lee, Seonock; Kim, Gamin; Kim, Jungho (Frontiers in Cell and Developmental Biology, 2023)
Testicular germ cell tumors (TGCTs) frequently affect adolescent and young adult males. Although TGCT is more responsive to cisplatin-based chemotherapy than other solid tumors, some patients are nonresponders, and following treatment, many patients continue to experience acute and long-term cytotoxic effects from cisplatin-based chemotherapy.Consequently, it is imperative to develop new therapeutic modalities for treatment-resistant TGCTs. Peptidyl-prolyl isomerase (Pin1) regulates the activity and stability of many cancerassociated target proteins. Prior findings suggest that Pin1 contributes to the pathogenesis of multiple human cancers. However, the specific function of Pin1 in TGCTs has not yet been elucidated. TGCT cell proliferation and viability were examined using cell cycle analysis and apoptosis assays following treatment with KPT6566, a potent, selective Pin1 inhibitor that covalently binds to the catalytic domain of Pin1. A xenograft mouse model was used to assess the effect of KPT6566 on tumor growth in vivo. KPT6566 effectively suppressed cell proliferation, colony formation, and ATP production in P19 and NCCIT cells. Further, KPT6566 induced apoptotic cell death by generating cellular reactive oxygen species and downregulating the embryonic transcription factors Oct-4 and Sox2. Finally, KPT6566 treatment significantly reduced tumor volume and mass in P19 cell xenografts. The Pin1 inhibitor KPT6566 has significant antiproliferative and antitumor effects in TGCT cells. These findings suggest that Pin1 inhibitors could be considered as a potential therapeutic approach for TGCTs.